THE EFFECTIVENESS OF THE PAIR CHECK TYPE OF COOPERATIVE LEARNING MODEL AND THE THINK PAIR SHARE ON THE LEARNING OUTCOMES - Hendun Prayogi; Romelan Hamzah (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
This study aims to determine whether or not the differences between mathematics learning outcomes with cooperative learning model of pair check and think pair share types and to compare the effectiveness of the two types in mathematics learning outcomes of students grade VII in even semester at Junior High School (SMP) Muhammadiyah 9 Yogyakarta in the academic year 2018/2019. This study is an experimental research that consists of experimental class 1 and experimental 2. The population is the student's class VII at SMP Muhammadiyah 9 Yogyakarta in 2018/2019. The sample was taken from 2 classes using a purposive sampling technique. The data collection technique in this study was using a method of learning outcomes tests and documentation. Before analyzing the data, a prerequisite test consisting of a normality test and testing the hypothesis in this study, two parties t-test were used with a significance level of 5%. The research outcomes at a significance level of 5% and df = 53 indicate no difference in mathematics learning outcomes using the cooperative learning model type of pair check with mathematics learning model type of think pair share. This is supported by the results of data analysis from the hypothesis test using the t-test. The results are , so it can be concluded that , so H0 is accepted, and H1 is rejected.